Impact of the trace element status on the course of ankylosing spondylitis in the Orenburg Region patients - U. A. Yakubova; O. V. Bugrova; S. I. Krasikov; N. P. Setko; R. I. Saifutdirov (Современная ревматология, 2019)
The role of trace elements (TEs) and their imbalance in the physiology of bone tissue and in the development of inflammatory diseases of the joints and spine has been discussed in recent years; however, there is no evidence for the TE status of patients with ankylosing spondylitis (AS) and its possible impact on the course of the disease.Objective: to investigate the impact of the TE status of patients with AS on the course, clinical manifestations, and activity of the disease.Patients and methods. Examinations were made in 58 patients (39 men and 19 women), residents of the Orenburg Region, with a reliable diagnosis of AS, the duration of which was 16 [11; 26] years. The patients’ mean age was 38 [31; 48] years. HLA-B27 antigen was detected in 91.4% of cases. In addition to the generally accepted examination, atomic absorption spectrophotometry was used to determine the hair levels of 9 TEs: Cu, Zn, Fe, Mn, Cr, Co, Ni, Pb, and Cd in all the patients.Results and discussion. The AS patients living in the Orenburg Region showed TE imbalance manifested by Cu and Zn deficiency and Ni, Cr, and Mn accumulation in the hair. Multidirectional correlations were found between the values of these TEs and the presence of extra-axial (peripheral arthritis, dactylitis) and extra-skeletal (uveitis) manifestations of AS, its activity, and severity of functional disorders.Conclusion. The preliminary results may suggest that the emerging imbalance of TEs can affect the course of AS, maintaining and increasing its activity.